2007
DOI: 10.1177/1352458507076961
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis susceptibility and the X chromosome

Abstract: Multiple sclerosis (MS) is a chronic autoimmune complex trait with strong evidence for a genetic component. A female gender bias is clear but unexplained and a maternal parent-of-origin effect has been described. X-linked transmission of susceptibility has been previously proposed, based on pedigree, association and linkage studies. We genotyped 726 relative pairs including 552 affected sib-pairs for 22 X-chromosome microsatellite markers and a novel dataset of 195 aunt-uncle/niece-nephew (AUNN) affected pairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…An increase in the female bias of MS has been observed in the United States (26,77), Canada (28,30), Australia (78), the United Kingdom (29,79), Norway (27,80), and Sardinia (81), due to an increased incidence among women, rather than to a decreased incidence among men. One explanation for the female bias could be X-linked risk factors, but extensive X chromosome linkage studies have not revealed MS susceptibility loci (82), and the rapidity of the femaleto-male sex ratio increase argues against a genetic origin (28). Another explanation for the female bias in MS invokes sex hormone-determined differences in immune responsiveness (25).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the female bias of MS has been observed in the United States (26,77), Canada (28,30), Australia (78), the United Kingdom (29,79), Norway (27,80), and Sardinia (81), due to an increased incidence among women, rather than to a decreased incidence among men. One explanation for the female bias could be X-linked risk factors, but extensive X chromosome linkage studies have not revealed MS susceptibility loci (82), and the rapidity of the femaleto-male sex ratio increase argues against a genetic origin (28). Another explanation for the female bias in MS invokes sex hormone-determined differences in immune responsiveness (25).…”
Section: Discussionmentioning
confidence: 99%
“…Extensive X-chromosome linkage studies have not revealed MS susceptibility loci, suggesting that X-linked risk factors probably do not explain the female sex bias [281]. Moreover, the three-fold increase in MS incidence among young women in the last half-century is not consistent with a genetic origin [270].…”
Section: Vitamin D Estrogen Eae and Multiple Sclerosismentioning
confidence: 99%
“…A recent molecular genetics study using data from the CCPGSMS [60] looked at 552 sib-pairs and 195 aunt-uncle/niece-nephew (AUNN) pairs who were genotyped for 22 X-chromosome microsatellite markers as well as a novel dataset of 18 markers. Parent-of-origin effects were explored by dividing AUNN families into maternal and paternal.…”
Section: Gender X-chromosome and Msmentioning
confidence: 99%
“…Together, the combined dataset gave exclusion at λ = 1.6. The study [60] concluded the following with the caveat that complex interactions, including epigenetic ones and masking balanced polymorphisms could not be excluded by the study design:…”
Section: Gender X-chromosome and Msmentioning
confidence: 99%